2017
DOI: 10.1016/j.neuroimage.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Creative constraints: Brain activity and network dynamics underlying semantic interference during idea production

Abstract: Functional neuroimaging research has recently revealed brain network interactions during performance on creative thinking tasks—particularly among regions of the default and executive control networks—but the cognitive mechanisms related to these interactions remain poorly understood. Here we test the hypothesis that the executive control network can interact with the default network to inhibit salient conceptual knowledge (i.e., pre-potent responses) elicited from memory during creative idea production. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
150
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 87 publications
13
150
3
1
Order By: Relevance
“…LSA has also been used on other semantic creativity tasks to measure the remoteness of associations (Beaty, Christensen, Benedek, Silvia, & Schacter, 2017;Green, 2016;Prabhakaran, Green, & Gray, 2014). For instance, Prabhakaran et al (2014) examined the semantic distance of verbs from nouns that were produced during a verb generation task.…”
Section: Divergent Thinking Divergent Thinking (Dt) Is a Common Proxmentioning
confidence: 99%
“…LSA has also been used on other semantic creativity tasks to measure the remoteness of associations (Beaty, Christensen, Benedek, Silvia, & Schacter, 2017;Green, 2016;Prabhakaran, Green, & Gray, 2014). For instance, Prabhakaran et al (2014) examined the semantic distance of verbs from nouns that were produced during a verb generation task.…”
Section: Divergent Thinking Divergent Thinking (Dt) Is a Common Proxmentioning
confidence: 99%
“…An increasing number of studies have examined how the DN interacts with other brain networks during tasks involving imagination. Research on creative cognition has found that the DN interacts with brain systems associated with cognitive control during tasks requiring the generation and evaluation of novel ideas (Beaty, Benedek, Kaufman, & Silvia, ; Beaty, Christensen, Benedek, Silvia, & Schacter, ; Ellamil, Dobson, Beeman, & Christoff, ; Mayseless, Eran, & Shamay‐Tsoory, ). In a recent study of divergent thinking, for example, Beaty et al () found that core default regions, e.g., the posterior cingulate cortex, showed increased functional connectivity with regions of the executive control network (ECN; right dorsolateral prefrontal cortex) and the salience network (SN; bilateral insula).…”
Section: Imagination and Brain Dynamicsmentioning
confidence: 99%
“…And lastly, structural connectivity analysis using tract-based spatial statistics (TBSS) seems to show diagnostic reasoning training inducing significant structural changes in the occipitotemporal part of middle temporal gyrus (MTG). As hypothesized, these findings suggest the transition of novices' whole-brain activity and connectivity during diagnostic reasoning from regions implicated in creative semantic processing (MFG/IOpFG, MTG and AG) 44,45 before training to regions implicated in improvised rule-based problem solving (cerebellum and POG, MSFG and MCG 17,[46][47][48] ) after training.…”
Section: Discussionmentioning
confidence: 82%
“…The activations of L-MFG/IOpFG have been consistently shown in neuroimaging studies of creative semantic cognition. For instance, Beaty et al 45 have revealed the involvement of both regions in generating unstudied (lowconstraint) and novel (high-constraint) semantically related words. In addition, Zhou et al 46 found that searching for numerical relations among conceptual knowledge while solving mathematical problems elicits greater activations in the L-IOpFG, AG, MTG, FuG, PHG, MSFG and posterior cingulate gyrus (PCG).…”
Section: Discussionmentioning
confidence: 99%